Investigation of the Impact of STEM Education on the Creative Design Skills of Prospective Teachers - OZKAYA, Ali; BULUT, Sait; SAHIN, Gizem (Asian Journal of Contemporary Education, 2022)
This study aims to evaluate the impact of STEM education on the creative design skills of trainee teachers. The sample for the study was made up of third-year prospective teachers studying at the Department of Science Education and Department of Elementary Mathematics Education in the 2020-2021 school year. Embedded mixed design, which is a type of mixed method, was used in the method of the study while the quantitative part of the mixed design was comprised of a one-group pretest-posttest design and the qualitative part was the case study. The implementation was carried out creating lesson plans aimed at STEM activities and process designs, and obtaining products throughout the course of one semester. Looking at the findings of this study, there were significant differences in favour of the posttest scores in all scales. Therefore, the conclusion was reached that the trainee teachers in both groups were observed to have experienced higher self-efficacy in terms of STEM practices, and that, in view of the meaningful rise in the sub-dimensions of the scales, the implementation was found to support the material design process and creativity. Examination of the qualitative data showed the codes support the changes that occurred in the quantitative data. Also, difficulties faced the trainee teachers were examined.